PENINGKATAN LITERASI STRATEGI PEMASARAN DI ERA DIGITAL PADA USAHA MIKRO KECIL DAN MENENGAH - Didi Sujadi; A.Asrorudin; Maman Darmansyah (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
This community service aims to improve marketing strategy literacy in the digital era for micro, small and medium enterprises at the Pendawa Islamic Boarding School. Bogor This is due to the increasingly competitive business world today. Based on this, in order to win the competition in the market in meeting the needs of the community for a similar product, every business actor must have a competitive advantage and have the right marketing strategy. The method used is qualitative descriptive to create systematic, factual and accurate descriptions and descriptions of the facts and relationships between phenomena. The results of this community service are expected that micro, small and medium business actors will be able to understand the internal and external factors of their business in analyzing the market, and the right marketing strategy so as to increase the company's profitability. And through a digital marketing strategy that is right on target in segmentation, it can influence the sales of MSME products and be able to attract customer interest in making purchasing decisions.